Useful strategies for reducing mental health stigma in healthcare settings: a Delphi study - Chávez, Lorena Paola; Zamorano, Sara; González-Sanguino, Clara; Muñoz, Manuel (Psychology, Society & Education, 2025)
Healthcare settings’ stigma towards mental health problems is a public health phenomenon that is attracting increasing research interest. Our aim was to identify useful strategies for reducing stigma towards mental disorders in healthcare settings. A qualitative study was carried out to reach an inter judge agreement among experts on these strategies, with a n = 23 experts in mental health stigma and clinical practice from Argentine and Spain. Consensus was reached on useful strategies for mental health stigma reduction in health and social contexts. Training in communication skills and empathy is the most useful strategy reported, followed by multidisciplinary work and supervision of clinical practices. It is advisable to promote the implementation of communication and empathy strategies during the education and training of health and social professionals to reduce stigma.